Band structure engineering of interfacial semiconductors based on atomically thin lead iodide crystals - Sun, Yan (2021)
To explore new constituents in two-dimensional (2D) materials and to combine their best in van der Waals heterostructures is in great demand as being a unique platform to discover new physical phenomena and to design novel functionalities in interface-based devices. Herein, PbI2 crystals as thin as a few layers are synthesized, particularly through a facile low-temperature solution approach with crystals of large size, regular shape, different thicknesses, and high yields. As a prototypical demonstration of band engineering of PbI2-based interfacial semiconductors, PbI2 crystals are assembled with several transition metal dichalcogenide monolayers. The photoluminescence of MoS2 is enhanced in MoS2/PbI2 stacks, while a dramatic photoluminescence quenching of  WS2 and WSe2 is revealed in WS2/PbI2 and WSe2/PbI2 stacks. This is attributed to the effective heterojunction formation between PbI2 and these monolayers; type I band alignment in MoS2/PbI2 stacks, where fast-transferred charge carriers accumulate in MoS2 with high emission efficiency, results in photoluminescence enhancement, and type II in WS2/PbI2 and WSe2/PbI2 stacks, with separated electrons and holes suitable for light harvesting, results in photoluminescence quenching. The results demonstrate that MoS2, WS2, and WSe2 monolayers with similar electronic structures show completely distinct light–matter interactions when interfacing with PbI2, providing unprecedented capabilities to engineer the device performance of 2D heterostructures.